Природньо-кліматичні особливості прирічкових територій міста Ужгород та специфіка їх розвитку - Боршовський, Олег; Borshovskyy, Oleh (Видавництво Львівської політехніки, 2021)
У статті досліджуються природно-кліматичні особливості регіону та міста Ужгород, які впливають на специфіку розвитку прирічкових територій. Річка Уж формується у гірському ландшафті Карпат. Функціонування екосистеми річки змінюється при виході її на пологі тераси та рівнину. Антропогенний тиск міста зумовлює збільшення проблем у процесі її самовідтворювальності. Розвиток міста, передбачений генеральним планом, архітектурно-планувальні засоби, ініціативи мешканців визначають в’язки і відносини між основними складовими системи: річки, міста і людини

The article examines the natural and climatic features of the region and the city of Uzhhorod, which affect the specifics of the development of near riverside areas. The Uzh River is formed in the mountainous areas of the Carpathians. The functioning of the river ecosystem changes when it reaches the sloping terraces and plains. Anthropogenic pressure of the city causes an increase of problems in the process of its self-reproduction. The development of the city, provided by the Master plan of the city, architectural and planning means and initiatives of the city residents determine the connections and relationships between the main components of the system: river, city and man. Architectural and spatial approaches to the design of a harmoniously integrated system of the river and the city are based on its self-reproduction as part of nature, primarily from a biological standpoint. Also, modern global urban trends in the opening of cities to rivers and the design of new "waterfront" of cities contribute to the cleaning of rivers and landscaping of surrounding areas. In the Master plan of the city of Uzhhorod, the landscape and recreational zones occupy an important place. The zones of the objects of the nature reserve fund are defined to ensure the preservation of unique natural landscapes with special conditions of use. Recreational zones of active entertainment are the urban areas of common use with appropriate objects for active recreation of the citizens as well as community centres. Considering the existing transport connections of Uzhhorod and pedestrian paths to the embankment territories, their location almost in the middle of the city as a coherence of the periphery with the central area of the city, the idea of creating a single system of embankment areas of the city was worked out, which will be interconnected by barrier-free bicycle tracks and pedestrian paths.
Natural and climate features of the river territories of the city of Uzhhorod and specifics of their development
Keywords: Ужгород; річка Уж; генеральний план міста; прибережні території; природно-відновлювальні процеси; благоустрій та облаштування; Uzhhorod; Uzh river; general plan of the city; coastal territories; nature restoration processes; improvement and arrangement; 711.2; 711.43; 551.58(477.87)